Assessing the ability of Ukrainian higher education to offer key skills of tomorrow - Oksana Zakharova; Liudmyla Usyk; Maryna Petchenko (Problems and Perspectives in Management)
Ukraine must search for efficient tools to accelerate the economic recovery in the post-war period. The workforce equipped with future skills is globally considered to be able to accelerate the pace of innovative growth and achieve the goals of Industry 4.0. This study aims to identify key skills of tomorrow and outline the ways in which these skills can be strengthened at Ukrainian universities. The skills of tomorrow that the Ukrainian standard for higher education recommends the universities include in the existing and new educational programs in various specialties were divided into five groups depending on their nature. Moreover, they were mapped following sustainable development goals to comprehensively assess their ability to promote each goal. Thus, the concept of a ‘future skill’ has been defined to contain aspects such as sustainability, skills, Industry 4.0, energy, education, energy efficiency, productivity, and creativity. The relationships between each future skill and its ability to facilitate sustainable development goals were described, and possible problematic areas were identified. Finally, the paper revealed that the skills able to boost the economy, which is specifically relevant for the post-war recovery of Ukraine, are not satisfactorily represented in Ukrainian higher education. Therefore, to make the Ukrainian higher education system a decisive factor in post-war recovery, it should shift the focus from solely hard skills to the skills of the future.